2019
DOI: 10.1016/j.heliyon.2019.e02214
|View full text |Cite
|
Sign up to set email alerts
|

Status of malondialdehyde, catalase and superoxide dismutase levels/activities in schoolchildren with iron deficiency and iron-deficiency anemia of Kashere and its environs in Gombe State, Nigeria

Abstract: Background Iron-deficiency anemia (IDA) or iron deficiency (ID) is by far the most common form of disorder affecting the cognitive development, physical growth and school performance of children in developing countries including Nigeria. Objectives In the present study, we aimed to examine whether IDA or ID, or both are associated with oxidative stress or otherwise by assessing the perturbations in oxidative stress markers including malondialdehyde (MDA), catalase (CAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…This can be an adaptive mechanism during the oxidative stress context of anemia, whereby sustained increased levels of erythrocyte H 2 O 2 induce GPx and other antioxidant enzymes 24 , 43 , resulting in an increased redox status. However, considerable variations exist in human studies with regard to ID and redox status 44 , which can be attributed to the study differences in sample size, age of subjects, distribution of males and females in the sample, and severity of ID. For example, Altun et al 24 found no increase in GPx activity in groups of infants with IDA when compared with aged-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…This can be an adaptive mechanism during the oxidative stress context of anemia, whereby sustained increased levels of erythrocyte H 2 O 2 induce GPx and other antioxidant enzymes 24 , 43 , resulting in an increased redox status. However, considerable variations exist in human studies with regard to ID and redox status 44 , which can be attributed to the study differences in sample size, age of subjects, distribution of males and females in the sample, and severity of ID. For example, Altun et al 24 found no increase in GPx activity in groups of infants with IDA when compared with aged-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Dalam proses belajar, pengetahuan seseorang diperoleh dengan melibatkan semua panca indera (Hussain et al, 2018) Semakin banyak seseorang memperoleh informasi akan semakin kompleks pengetahuan yang didapatkan (Julaecha, 2020). Dalam menunjang pengetahuan yang kompleks dalam proses belajar dibutuhkan beberapa penunjang seperti penggunaan media sebagai alat bantu yang disebut media komunikasi (Sharif Usman et al, 2019).…”
Section: Pembahasanunclassified
“…The production of hemoglobin and other iron-containing proteins such as cytochrome, myoglobin, catalase and peroxidase is also affected in ID (3,4). In addition, studies have shown decreases in concentrations and activities of antioxidant enzymes such as glutathione peroxidase (GSH-Px), catalase (CAT) and superoxide dismutase (SOD) in patients with IDA, thus reducing the total antioxidant capacity (TAC) (5,6).…”
Section: Introductionmentioning
confidence: 99%